The influence of consulting primary care on knee pain in older people: a prospective cohort study. Issue 12 (31st January 2008) - Blagojevic, M; Jinks, C; Jordan, K P
Abstract : Objective: To investigate whether consulting a general practicioner (GP) in the 3 years after reporting knee pain is linked to better knee pain outcomes (reduced presence or severity of knee pain) at the end of the 3 year period. Methods: We undertook a population-based cohort study linking baseline (2000) and follow-up (2003) surveys to primary care medical records. The cohort comprised 1577 adults aged 50 and over registered at 3 general practices in North Staffordshire, UK, who reported knee pain in a baseline survey. The main outcome measures were self-reported prevalence of knee pain and severity of knee pain in the follow-up survey. The relationship between consultation and future knee pain status was adjusted for an individual's propensity to consult given related demographic and health-related factors. Results: In persons who consulted for knee pain, 91% reported knee pain at 3 years, compared with 73% of those who did not consult (adjusted odds ratio (OR) 2.25; 95% CI 1.56 to 3.26). Among persons reporting severe knee pain or disability at baseline (n = 669), those who consulted for knee pain were more likely to report severe knee pain or disability at 3 years than those who did not consult (82% v 65%, adjusted OR 1.93; 95% CI 1.27 to 2.93). Conclusions: Older adults with knee pain continue to have persistent problems regardless of whether they consult primary care or not. Further research is needed to identify more effective means of reducing the burden of knee pain in the community.